ZnTe cryogenic scintillator - Mikhailik, V; Galkin, S; Kraus, H; Mokina, V; Hrytsak, A; Kapustianyk, V; Panasiuk, M; Rudko, M; Rudyk, V (Elsevier, 2017)
The X-ray luminescence and scintillation properties of undoped ZnTe crystal were investigated as function of temperature down to T<10 K. The luminescence of ZnTe is quenched at room temperature, but below 150 K the crystal exhibits emission at 575 nm with characteristic recombination decay kinetics. The emission is attributed to the radiative annihilation of electrons captured at the shallow levels of impurities or defects with holes trapped by Zn vacancies. The temperature dependence of scintillation light output of ZnTe was studied. It was found that at excitation with α-particles the light output of undoped ZnTe is 117±20% of a reference CaWO4 crystal measured under the same experimental conditions. It is concluded that undoped zinc telluride is a promising scintillator for cryogenic application, particularly for the cryogenic search for neutrinoless double beta decay (0νDBD) of 130Te.